2023
DOI: 10.1111/jns.12564
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 1 overexpression rescues the abnormal mitochondrial dynamics caused by the Mitofusin 2 K357T mutation in vitro

Abstract: Background and aimsMitofusin 1 (MFN1) and MFN2 are outer mitochondrial membrane fusogenic proteins regulating mitochondrial network morphology. MFN2 mutations cause Charcot‐Marie‐Tooth type 2A (CMT2A), an axonal neuropathy characterized by mitochondrial fusion defects, which in the case of a GTPase domain mutant, were rescued following wild‐type MFN1/2 (MFN1/2WT) overexpression. In this study, we compared the therapeutic efficiency between MFN1WT and MFN2WT overexpression in correcting mitochondrial defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Indeed, in vitro studies have demonstrated that MFN1 has the capacity to compensate for the loss of MFN2, safeguarding against mitochondrial fusion and transport defects induced by mutations in MFN2. 5 , 76 These data have been also confirmed in the Thy1.2‐MFN2R94Q transgenic mice expressing the point mutant R94Q on MFN2 specifically in neurons under the Thy1.2 promoter. 50 , 77 These mice recapitulate a range of neurological features observed in CMT2A.…”
Section: Therapeutic Implicationsmentioning
confidence: 63%
“…Indeed, in vitro studies have demonstrated that MFN1 has the capacity to compensate for the loss of MFN2, safeguarding against mitochondrial fusion and transport defects induced by mutations in MFN2. 5 , 76 These data have been also confirmed in the Thy1.2‐MFN2R94Q transgenic mice expressing the point mutant R94Q on MFN2 specifically in neurons under the Thy1.2 promoter. 50 , 77 These mice recapitulate a range of neurological features observed in CMT2A.…”
Section: Therapeutic Implicationsmentioning
confidence: 63%